1976
DOI: 10.1111/j.1365-2044.1976.tb11970.x
|View full text |Cite
|
Sign up to set email alerts
|

The administration of metoclopramide with atropine A drug interaction effect on the gastro–oesophageal sphincter in man

Abstract: A zone of increased intraluminal pressure exists at the gastro-oesophageal junction in man, and is believed to act as a physiological sphincter. Contraction of this lower oesophageal sphincter (LOS), probably prevents reflux of acid gastric content. ' The mechanisms involved in maintaining gastro-oesophageal competence remain controversial. Three mechanisms, independent of the LOS have been invoked in the prevention of reflux.2 These are the pinch-cock action of the diaphragm, the flap valve effect of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 11 publications
2
14
1
1
Order By: Relevance
“…(26) found that, without cricoid pressure, metoclopramide significantly increased the pop‐off point during manual ventilation, while atropine significantly decreased the pop‐off point. This is also supported by previous motility studies (27–29).…”
Section: When Should Cricoid Pressure Be Applied: Before or Shortly Asupporting
confidence: 92%
“…(26) found that, without cricoid pressure, metoclopramide significantly increased the pop‐off point during manual ventilation, while atropine significantly decreased the pop‐off point. This is also supported by previous motility studies (27–29).…”
Section: When Should Cricoid Pressure Be Applied: Before or Shortly Asupporting
confidence: 92%
“…The concurrent administration of anticholinergic drugs, pramlintide, for example, is known to decrease the effectiveness of metoclopramide, and such medications were not administered in our cases [10]. There was also no administration of drugs that may interfere with the actions of levodopa, such as haloperidol, loxapine, phenothiazines, in our cases.…”
Section: Discussionmentioning
confidence: 86%
“…Brock‐Utne et al . administered the combination of atropine 0.6 mg and metoclopramide 10 mg in healthy volunteers, and demonstrated unaltered LOS pressure (10). Similarly, the same group of investigators showed that metoclopramide given before or after atropine antagonized the LOS pressure‐lowering effect of atropine in healthy subjects (11).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, i.v. metoclopramide alone increases LOS tone in dogs and human adults (9,10). Thus, metoclopramide may antagonize the detrimental effect of atropine on the LOS pressure in anaesthetized children, as seen in adults (11).…”
Section: Introductionmentioning
confidence: 99%